Pengaruh Budaya Kerja, Beban Kerja dan Work Family Conflict terhadap Kinerja Karyawan: Studi Pada PT Perusahaan Listrik Negara (Persero) Unit Pelaksana Pengatur Beban (UP2B) Sistem Minahasa - Junaedi Junaedi; Saepudin Saepudin; Yanti Hasbian Setiawan; Ika Kartika (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This research was conducted at PT. PLN (Persero) Minahasa System Load Regulatory Implementation Unit (UP2B). Based on the data found, the achievement of employee performance at PT. PLN (Persero) UP2B Minahasa system looks not optimal. This study takes a theme entitled, Influence of Work Culture, Workload and Work Family Conflict on Employee Performance (Study at P.T. State Electricity Company (Persero) Load Regulatory Implementing Unit (Up2b) Minahasa System). This study aims to analyze the influence of organizational culture, workload and leadership style on employee performance. The object of this research is all employees of PT. State Electricity Company (Persero) Minahasa Systems Load Regulatory Unit (UP2B). This research was conducted on 98 respondents using a quantitative descriptive approach. The method of data analysis is done by Partial Least Square analysis. The results of the study show that organizational culture has a positive and significant effect on employee performance. Workload has a negative and significant effect on employee performance and Work Family Conflict has a positive and negative effect and is not significant on employee performance. Keywords: Work Culture, Workload, Work Family Conflict, Employee Performance, State Electricity Company Minahasa System